DSD: A Discussion at the Crossroads of Medicine, Human Rights, and Politics - De Sutter, Petra (Frontiers in Pediatrics, 2020)
Over the past years, the topic of ‘disorder/differences in sex development (DSD)’ or ‘intersex’ people has become subject of the international political agenda. In 2017, a resolution of the Parliamentary Assembly of the Council of Europe argued that the practice of surgically modifying intersex children’s genitals without medical necessity and without consent of the person concerned is a human rights violation. This resolution and related statements might impact heavily on pediatric urologists and their practice. While this resolution concerns a form of soft law and is not directly enforceable in member states, it might impact the national debates concerning legislation and medical guidelines on DSD. Consequently, this article reflects on this discussion by elaborating on the importance of human rights in our evolving understanding and legislation on DSD and other gender and sexuality issues in general. It constitutes a plea for a dialogue between medical professionals, lawmakers and human rights scholars, which would lead to legislation and medical guidelines that take a holistic and rights-based approach.